2014
DOI: 10.1080/10255842.2014.980820
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of muscle forces in gait using a simulation of the electromyographic activity and numerical optimization

Abstract: Clinical gait analysis provides great contributions to the understanding of gait patterns. However, a complete distribution of muscle forces throughout the gait cycle is a current challenge for many researchers. Two techniques are often used to estimate muscle forces: inverse dynamics with static optimization and computer muscle control that uses forward dynamics to minimize tracking. The first method often involves limitations due to changing muscle dynamics and possible signal artefacts that depend on day-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…40 Indeed, previous studies have reported that people with MS have greater variability in gait mechanics compared with controls, [41][42][43] and, therefore, the variability in the magnitude of adaptations measured in the present study may reflect differences in lower limb muscle activation and gait mechanics among participants. Although studies using electromyography have demonstrated reduced gastrocnemius activation during push-off compared with controls, 41,44 the improvement in oxidative capacity observed in the present study suggests that the voluntary activation of the gastrocnemius muscle during the antigravity treadmill training was sufficient to initiate the biochemical pathways required for mitochondrial biogenesis. 45 Reductions in muscle oxidative capacity may be related to walking dysfunction in people with MS, 7,13,40 and the present findings lend support to the use of antigravity treadmill training in interventions aiming to improve muscle oxidative metabolism in people with MS who have significant walking impairments.…”
Section: Discussioncontrasting
confidence: 73%
“…40 Indeed, previous studies have reported that people with MS have greater variability in gait mechanics compared with controls, [41][42][43] and, therefore, the variability in the magnitude of adaptations measured in the present study may reflect differences in lower limb muscle activation and gait mechanics among participants. Although studies using electromyography have demonstrated reduced gastrocnemius activation during push-off compared with controls, 41,44 the improvement in oxidative capacity observed in the present study suggests that the voluntary activation of the gastrocnemius muscle during the antigravity treadmill training was sufficient to initiate the biochemical pathways required for mitochondrial biogenesis. 45 Reductions in muscle oxidative capacity may be related to walking dysfunction in people with MS, 7,13,40 and the present findings lend support to the use of antigravity treadmill training in interventions aiming to improve muscle oxidative metabolism in people with MS who have significant walking impairments.…”
Section: Discussioncontrasting
confidence: 73%
“…The magnitude of knee and ankle JCF in our study was relatively higher than those reported in walking. The reason could be that EMG signal was supplemented to the modeling in our study to account for muscle physiology and co-contraction, while some other studies may underestimate the joint loading based on a purely mathematical solution [ 46 ]. Our results showed that JCF was similar across the three conditions, except that peak ankle JCF in the shear direction was higher in flip-flops than sports shoes.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, biomechanical analysis of the human locomotor system by applying rigid-body musculoskeletal models has strongly increased in the research community with the primary objective of analyzing the influence of muscle activations for different body movements. [3][4][5][6] At the same time, FE method has emerged as a complementary approach (in both in vivo and in vitro studies) for analyzing the mechanical behavior of joints, muscles and skeletal tissues. [7][8][9][10] These computational models can provide estimates of stress and strain data over the entire area of interest, which becomes especially advantageous for locations where it may be difficult or impossible to obtain experimental measurements.…”
Section: Introductionmentioning
confidence: 99%